C -reactive protein in assessment of severity acute pancreatitis (Journal of Surgical Sciences, 2020)
Background: Acute pancreatitis (AP) is an acute inflammation of the pancreas and clinical evolution is frequently unpredictable. Numerous predictive markers have been studied to assess severity in AP, including clinical assessment, clinical-physiological scoring systems, imaging techniques, and biochemical markers in different body fluids.Objective: This study was done to see the association between level of CRP and severity of acute pancreatitis. Methods: 50 patients diagnosed as acute pancreatitis based on operational definition admitted in Dhaka Medical College Hospital was included in the study. Patients' admission date back from 1ST August, 2016 to 31december, 2015. Conservative management started from the date of admission as per standard conservative management protocol. Patients were monitored by RANSON scoring system and categorized as mild if RANSON score is